Low-dose BPA exposure alters the mesenchymal and epithelial transcriptomes of the mouse fetal mammary gland. - Perinaaz R Wadia (Public Library of Science (PLoS), 2013)
Exposure of rodent fetuses to low doses of the endocrine disruptor bisphenol A (BPA) causes subtle morphological changes in the prenatal mammary gland and results in pre-cancerous and cancerous lesions during adulthood. To examine whether the BPA-induced morphological alterations of the fetal mouse mammary glands are a) associated with changes in mRNA expression reflecting estrogenic actions and/or b) dependent on the estrogen receptor α (ERα), we compared the transcriptomal effects of BPA and the steroidal estrogen ethinylestradiol (EE2) on fetal mammary tissues of wild type and ERα knock-out mice. Mammary glands from fetuses of dams exposed to vehicle, 250 ng BPA/kg BW/d or 10 ng EE2/kg BW/d from embryonic day (E) 8 were harvested at E19. Transcriptomal analyses on the ductal epithelium and periductal stroma revealed altered expression of genes involved in the focal adhesion and adipogenesis pathways in the BPA-exposed stroma while genes regulating the apoptosis pathway changed their expression in the BPA-exposed epithelium. These changes in gene expression correlated with previously reported histological changes in matrix organization, adipogenesis, and lumen formation resulting in enhanced maturation of the fat-pad and delayed lumen formation in the epithelium of BPA-exposed fetal mammary glands. Overall similarities in the transcriptomal effects of BPA and EE2 were more pronounced in the epithelium, than in the stroma. In addition, the effects of BPA and EE2 on the expression of various genes involved in mammary stromal-epithelial interactions were suppressed in the absence of ERα. These observations support a model whereby BPA and EE2 act directly on the stroma, which expresses ERα, ERβ and GPR30 in fetal mammary glands, and that the stroma, in turn, affects gene expression in the epithelium, where ERα and ERβ are below the level of detection at this stage of development.